2018
DOI: 10.1155/2018/4197659
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture at Tiaokou (ST38) for Shoulder Adhesive Capsulitis: What Strengths Does It Have? A Systematic Review and Meta‐Analysis of Randomized Controlled Trials

Abstract: Objective Tiaokou (ST38) is used as a crucial distal acupoint for treating shoulder adhesive capsulitis (SAC) in traditional Chinese medicine. The objective of this study was to assess the effectiveness and safety of acupuncture at Tiaokou for treating SAC. Methods We searched eight electronic databases without language restrictions. All the literature was processed to identify RCTs comparing acupuncture at Tiaokou with other therapies (e.g., acupuncture at local shoulder acupoints and nonsteroidal anti-inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Local-distal acupoints such as Bladder 40 had been identified for specific disorders. These acupoints were found to be effective for the treatment of inflammationassociated disorders in comparison with local administration [21][22][23][24][25]. Dr. Tan's strategy applies a systemic approach to treat a patient.…”
Section: Therapeutic Potential Of Acupuncture In Chronic Inflammationmentioning
confidence: 99%
“…Local-distal acupoints such as Bladder 40 had been identified for specific disorders. These acupoints were found to be effective for the treatment of inflammationassociated disorders in comparison with local administration [21][22][23][24][25]. Dr. Tan's strategy applies a systemic approach to treat a patient.…”
Section: Therapeutic Potential Of Acupuncture In Chronic Inflammationmentioning
confidence: 99%
“…A meta-analysis in Chinese of 19 RCTs found encouraging evidence for the efficacy of acupuncture at the Tiaokou point in the treatment of shoulder stiffness [43]. Bee venom acupuncture likewise has for a long time been a traditional approach in oriental medicine for the relief of pain and inflammation.…”
Section: Acupuncturementioning
confidence: 99%
“…This method is named opposite needling. It refers to acupuncture points on the right side are selected for diseases on the left side and vice versa [16]. Many clinical trials have found that the therapeutic effect on shoulder pain by opposing needling at acupoint ST 38 is better than that by routine acupuncture treatment, such as in acupoints Jianzhen, Jianyu, and Jianliao [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Many clinical trials have found that the therapeutic effect on shoulder pain by opposing needling at acupoint ST 38 is better than that by routine acupuncture treatment, such as in acupoints Jianzhen, Jianyu, and Jianliao [17,18]. A systematic review suggests that acupuncture at contralateral ST 38 for shoulder pain achieved significant effects in improving the symptoms [16]. Unfortunately, its mechanisms of action are not well understood.…”
Section: Introductionmentioning
confidence: 99%